Trypanosoma (Megatrypanum) ornata sp. n., a Parasite of the Eurasian Water Shrew Neomys fodiens (Pennant, 1771) - Karbowiak, Grzegorz; Wita, Irena; Rychlik, Leszek (My University, 2005)
Infection with the new trypanosome species Trypanosoma ornata sp. n. was detected in water shrews Neomys fodiens examined for presence of blood parasites in September 2003 and 2004 in Białowieża Forest (eastern Poland). The prevalence of infection was about 36.3%. The trypanosomes occurred as trypomastigote forms only, the epimastigote, dividing forms or other developmental stages were not observed. The morphological features of the species (big body size, small kinetoplast located close to the cell margin, the presence of vermiform posterior end, the surface of the cell markedly striated with longitudinal ‘myonemes”, short free flagellum) support its affiliation to Megatrypanum subgenus. The detail morphometric characterization is given.
Keywords: Neomys fodiens; Trypanosoma ornata; Białowieża Forest